PENGARUH JOB SATISFACTION, PERCEIVED ORGANIZTIONAL SUPPORT, DAN EMPLOYEE CARE TERHADAP WORK ENGAGEMENT PADA KARYAWAN EKSPEDISI DI JAKARTA - Nurulita Fauzia Kamal; Netania Emilisa; Tiara Safitri (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Comfort in the workplace has a correlation with job satisfaction, trusted organizational support, employee care, influence on work involvement. Happy employees can increase company productivity and will give the best for their work. The purpose of this research is to prove the impact of work involvement in a shipping company in Jakarta. This research involved 127 employees at a shipping company in Jakarta. Data analysis using pearson product moment analysis. These results indicate that job satisfaction increases happiness at work. The implications of this study are expected that companies can increase employee work involvement in the workplace through increasing job satisfaction, trusted organizational support, employee care to influence work involvement